CHARACTER EDUCATION VALUES IN READING SECTION OF E-ENGLISH TEXTBOOK FOR SENIOR HIGH SCHOOL STUDENTS GRADE XI - Hapsari, Pratama Lysa (ELT Forum: Journal of English Language Teaching, 2013)
The main purpose of the study is to find out what character values are integrated in reading section of the English e-book of Senior High School and in which part of the English e-book of Senior High School the character values are realized. In order to obtain the objective of the study, I did several steps. I selected the e-book and then the reading section was selected. After selecting the reading section, the character education values integrated in the reading section were identified. Then, I identified the character education values in the reading section components; whether they are integrated in reading texts or reading exercises. From the eighteen character values formulated by The Indonesian Ministry of National Education 2010, there are only seventeen of them covered in reading section of the e-book. These seventeen values are honesty, tolerance, democracy, hard work, creativity, environmental caring, social caring, discipline, patriotism, nationalism, respect achievement, loving peace, reading habit, independence, religious, curiosity, and friendly/communicative. One character value that is not covered in reading sections is responsibility. All the character values found are covered in both components of the reading sections. After analyzing, I would like to suggest for the next researcher who attempts to do the similar research as I do. He/she should analyze the textbook which is recommended by the Book Centre (Pusbuk) of the National Education Ministry (Depdiknas) so that his/ her research will have a great possibility to be used as a consideration to select a good textbook for teaching and learning processes at schools.